A Comparative Study of Two Vietnamese Translations of ‘The Way of the White Clouds - Nguyen Yen Thanh (Trường Đại học Trà Vinh, 2018)
To explore the translation strategies applied by two Vietnamese translators through analyzing of the book’s title and the first 12 subtitles in Chapter 1 of The Way of the White Clouds; to provide appropriate translation strategies for Vietnamese learners of translation.